Effect of heat treatment on cold sprayed Ti-6Al-4V alloy - Mao, Mengyuan (2018)
In this dissertation, cold sprayed Ti-6Al-4V coatings were annealed at six different conditions to investigate the heat treatment effect. With the temperature increasing from 300 to 950 °C, the atomic diffusion between the particles continuously eliminated the pores in the coatings. And ultrafine grain could be found in the microstructure of coating heated at 950 oc. While both top surface and cross section of the coating could obtain the highest and lowest hardness at 400 oc and 9 50 °C, respectively. By simulating the particle deposition process in the ABAQUS finite element software, the stress and temperature profiles were evaluated. The single impact results showed that higher impact velocity led to higher stress and temperature, especially at the interface. Before the particle finally deposited on the substrate, the stress reduced by nearly 10% due to localized heat. And the second impact revealed that the interface of coating layer and substrate experienced much higher stress than other area, which could lead to cracks of the coating. In conclusion, heat treatment has significant influence on the microstructure and mechanical properties of cold sprayed Ti-6Al-4V coatings, and might has certain effect on the residual stress based on the simulation results.